2017
DOI: 10.11648/j.acm.20170604.13
|View full text |Cite
|
Sign up to set email alerts
|

Close Form Solutions of the Fractional Generalized Reaction Duffing Model and the Density Dependent Fractional Diffusion Reaction Equation

Abstract: Abstract:The two variable ( ⁄ , 1 ⁄ )-expansion method is significant for finding the exact traveling wave solution to nonlinear evolution equations (NLEEs) in mathematical physics, applied mathematics and engineering. In this article, we exert the two variable ( ⁄ , 1 ⁄ )-expansion method for investigating the fractional generalized reaction Duffing model and density dependent fractional diffusion reaction equation and obtain exact solutions containing parameters. When the parameters are taken particular valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We have also depicted some of the obtained solutions graphically (3D surface graphs and 2D line plots) and concluded that the results we obtained are accurate, efficient, and versatile in mathematical physics. It is worth to noticing that compared to previous works [25,26,44,45]; the results obtained in this paper are presented for the first time. Lastly, it can be concluded that our offered methods are more effective, reliable, and powerful, which give bounteous consistent solutions to NLPFDEs arise in different fields of nonlinear sciences.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…We have also depicted some of the obtained solutions graphically (3D surface graphs and 2D line plots) and concluded that the results we obtained are accurate, efficient, and versatile in mathematical physics. It is worth to noticing that compared to previous works [25,26,44,45]; the results obtained in this paper are presented for the first time. Lastly, it can be concluded that our offered methods are more effective, reliable, and powerful, which give bounteous consistent solutions to NLPFDEs arise in different fields of nonlinear sciences.…”
Section: Discussionmentioning
confidence: 56%
“…Density dependent fractional diffusion reaction equation which is widely used in mathematical biology in the form [44,45]…”
Section: Density Dependent Fractional Diffusion Reaction Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…e major challenges, however, are that there is no unified numerical or analytical approach that can investigate all sorts of nonlinear fractional-order differential equations. us, several numerical and theoretical methods for finding solutions for NLFDEs have been established, for example, the differential transformation method [6,7], the variational iteration method [8][9][10], the fractional subequation method [11], the Kudryashov [12] method, the homotopy perturbation method [13,14], the homotopy analysis method [15], the exp-function method [16,17], the (G ′ /G)-expansion method and its various modification [18][19][20][21][22], the Chelyshkov polynomial method [23,24], the multiple exp-function method [25], the finite difference method [26], the finite element method [27], the first integral method [28,29], the modified simple equation method [30], the reproducing kernel method [31], the two variables ((G ′ /G), (1/G))-expansion method [32,33], and the Picard technique [34].…”
Section: Introductionmentioning
confidence: 99%